Effects of bubble–liquid two‐phase turbulent hydrodynamics on cell damage in sparged bioreactor. (28th October 2013) - Liu, Yang; Li, Fanxing; Hu, Weiwei; Wiltberger, Kelly; Ryll, Thomas
<x xml:space="preserve">Abstract</x> According to recent experimental studies on sparged bioreactors, significant cell damage may occur at the gas inlet region near the sparger. Although shear stress was proposed to be one of the potential causes for cell damage, detailed hydrodynamic studies at the gas inlet region of gas–liquid bioreactors have not been performed to date. In this work, a second‐order moment (SOM) bubble–liquid two‐phase turbulent model based on the two‐fluid continuum approach is used to investigate the gas–liquid hydrodynamics in the bubble column reactor and their potential impacts on cell viability, especially at the gas inlet region. By establishing fluctuation velocity and bubble–liquid two‐phase fluctuation velocities correlation transport equations, the anisotropy of two‐phase stresses and the bubble–liquid interactions are fully considered. Simulation results from the SOM model indicate that shear and normal stresses, turbulent energy dissipation rate, and the turbulent kinetic energy are generally smaller at the gas inlet region when compared with those in the fully developed region. In comparison, a newly proposed correlation expression, stress‐induced turbulent energy production (STEP), is found to correlate well with the unusually high cell death rate at the gas inlet region. Therefore, STEP, which represents turbulent energy transfer to a controlled volume induced by a combination of shear and normal stresses, has the potential to provide better explanation for increased cell death at the sparger region. © 2013 American Institute of Chemical Engineers Biotechnol. Prog., 30:48–58, 2014